The Influence of Company Size, Profitability, Liquidity and Solvency on the Extent of Voluntary Disclosure in Agriculture and Mining Sector Companies Listed on Indonesian Stock Exchange for 2020-2022 Period - Apriliani, Cantika; Hizazi, Achmad; Ridwan, Muhammad (PT. Riset Press International, 2024)
The aim of this research is to determine how much voluntary freedom is influenced by company size, profitability, liquidity and solvency. The population of this research is agricultural and mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020–2022 period. Purposive sampling is the sampling method applied. 13 companies were the samples used in this research. The multiple linear regression analysis method was used in this research to analyze the data. Research findings show that the degree of freedom is influenced by solvency. Voluntary rates are not influenced by company size, profitability, or liquidity. The level of voluntary release is influenced by company size, profitability, liquidity and solvency simultaneously with an Adjusted R Square value of 0.162 or 16.2%, while the remaining 0.838 or 83.8% is influenced by other variables.